Dall’influenza della politica alla politica degli influencer - Mirra, Giulia; Pietropaoli, Matteo (SocietàMutamentoPolitica, 2024)
This work aims to face an issue that underlies the political dimension of today: to what extent politics and social media communication influence each other, to the point of provoking the constant contamination of the politician-influencer and influencer-politician figures. Through the reflection presented here, which starts from the theme of the infosphere and the swarm of citi-netizens in order to identify virtual hubs for the interpretation of reality, the authors will try to understand the cultural change that forces the commercial and the political figures to become opinion leader of both fields. This also in order to identify the characteristics of a profiled citizen-voter, made a participant without his knowledge, in a process of defining the political image that finds its fulcrum (and filter) precisely in the digital, where he is both producer and consumer (subject and object) of communication.